Analysis of safety specifications in risk management plan at the time of drug approval and addition of clinically significant adverse reactions in the package insert post‐approval in Japan - Rieko Saito; Seiko Miyazaki (Wiley, 2023)
Abstract Recently, post‐marketing safety measures have been considered critical in Japan due to the globalization of drug development and the introduction of new drug approval systems. Pharmacists are expected to play an active role in ensuring the safety of drugs post‐approval. Utilizing risk management plans (RMPs) to ensure safety throughout the development and post‐marketing phases is becoming even more critical. In this study, we examine the relationship between the safety specifications (SSs) in RMPs at the time of drug approval and the adverse reactions (ARs) added to the clinically significant adverse reactions (CSARs) section of the package inserts (PIs) post‐approval to determine whether SSs constitute useful drug information for pharmacists. The analysis included new active ingredient‐containing drugs approved in Japan from FY2013 to 2019. A 2 × 2 contingency table was created and analyzed using odds ratios (ORs) and Fisher's exact test. The OR was 14.22 (95% CI: 7.85-24.77; p < .001), which indicates a strong relationship between the ARs being SSs at the time of approval and being added to the PIs as CSARs post‐approval. The positive predictive value that SSs at the time of approval were added as CSARs to the PIs post‐approval was 7.1%. In addition, a similar relationship was observed with the "approval in shorter‐period drugs" reviewed for approval based on a limited number of clinical trials. Therefore, SSs in RMPs are important drug information for pharmacists in Japan.